A re-evaluation of the theme of fate in Sophocles' Oedipus Rex and Ola Rotimi's the Gods are not to blame (2020)
Intertextuality presupposes the linkage of subjects, ideas and themes between and among texts. Although numerous scholars have carried out intertextual readings into various texts, only a few have delved principally into cosmological connectives within texts from the cultural perspective of fatalism. The universality of the theme of fatalism and its rootedness in virtually every religion around the world necessitates this work. This study, therefore, investigates the textual hybridisation and thematisation of apparently contrasting worldviews (Greek and Yoruba) in order to improve the body of existing intertextual literature on fatalism. This study is anchored on the philosophical concept of determinism. Two texts were purposively selected- Sophocles' Oedipus Rex (OR), a classical play, and Ola Rotimi's The Gods are not to Blame (TGB), a contemporary play, for contextual and intertextual study. The study finds that TGB shares more than superficial semblance with OR though textual variations exist between both. TGB is considered a perfect hybrid that thematically draws parallels from OR, foregrounding the integral and unique religio-cultural affinity that exists between the Yoruba people of Western Nigeria and the Greek of the Classical era. Fatalism, being a fundamental aspect of the ancient Greek cosmology, was often thematised in Classical Greek writings as reflected in the text, OR. The study then concludes that the Yoruba people, like the ancient Greek, acknowledge the important role of fate as determinism in human life and as a reality beyond the control of the individual